A Single Institution Evaluation of the Performance of Two Different Chest Drainage Systems in Pediatric Patients after Surgery for Congenital Heart Disease - Vida, Vladimiro L.; Gallo, Michele; Barzon, Elisa; Olivato, Veruska; De Franceschi, Marco; Guariento, Alvise; Padalino, Massimo; Stellin, Giovanni (The Thoracic and Cardiovascular Surgeon, 2015)
Background The study compares the efficacy and advantages of two different drainage systems in pediatric patients during surgery for congenital heart disease (CHD).Methods A total of 200 consecutive pediatric patients (< 16 years) were enrolled; in 100 patients we used a polyvinyl chloride drain (PVCD) and in the other 100 we used a silicone drain (SD). Demographics, drain's technical data, and postoperative complications and costs were evaluated. A pain score was calculated in patients older than 6 years.Results The SDs were significantly smaller when compared with PVCDs (median of 1.63 vs. 3.09 French/kg, p = 0.0006), were kept in site for a median shorter period (23 vs. 40 hours, p = 0.002), drained more thoracic spaces (median of 2 vs. 1, p < 0.0001), and were associated to a lower pain score (p = 0.01). The overall drain-related complication rate was lower for the SD group than for the PVCD group (3 vs. 9%, p = 0.1) as well as the drain-related adverse event required additional interventional maneuvers (0 vs. 6%, p = 0.04). Patients who were treated with a PVCD reported a higher perceived pain score than patients treated with a SD, both at the time when the drain was in site (p = 0.016) and during the drain's removal (p = 0.0001).Conclusion SDs can be used safely in pediatric patients during surgery for CHD. Sizes required are smaller than other conventional drains and multiple cavities can be drained with a single tube. The use of SD is associated to a lower complication rate, lower requirement of additional procedures, and lesser perceived pain from the patient, when compared with other more traditional drains.
Keywords: congenital heart disease; cardiac surgery; chest drainage